Bibliometric and visualization analysis of glioma pharmacotherapy from 2020 to 2024 - Hong, Xinjie; Wei, Zhentao; Zuo, Tian; Xu, Liyu; Zhang, Haohang; Xu, Tao; Wang, Dongmei; Lu, Chengyin; Hou, Lijun (Frontiers in Neurology, 2025)
ObjectiveGliomas are the most common and aggressive malignant tumors of the central nervous system. Their complex biology and adaptive resistance mechanisms pose major obstacles to existing treatment strategies. This study aims to analyze research published over the past 5 years to identify emerging trends, effective therapeutic agents, and novel treatment strategies.MethodsRelevant articles on glioma drug therapy were retrieved from the Web of Science Core Collection for the period 2020–2024. Bibliometric analyses were performed using CiteSpace and VOSviewer to examine authorship, institutional and national contributions, journal impact, and keyword distributions. A total of 9,701 articles were included in the analysis.ResultsChina leads in publication volume on glioma research, followed by the United States. Liu Yang from China is the most prolific author in this field over the past 5 years. Institutions from China and the United States are the primary contributors to this area of research. Bibliometric analysis identified four major thematic clusters: glioma treatment, drug delivery, immunotherapy and the tumor microenvironment, and the molecular mechanisms underlying glioma cell behavior.ConclusionThis systematic analysis of glioma treatment research over the past 5 years highlights key global research hotspots and emerging trends. Drug delivery and immunotherapy have gained increasing attention as promising therapeutic approaches. Advances in glioma treatment are expected to improve patient outcomes.